Antimicrobial Susceptibility Profile of Rare Anaerobic Bacteria - Lena Josephine Wolf; Catalina-Suzana Stingu (MDPI AG, 2022)
Anaerobes play an important role in clinically relevant infections and resistance is increasing worldwide. We tested 120 rare anaerobic isolates belonging to 16 genera for antimicrobial resistance using the agar dilution method and compared those results to the time-saving E-test method. The susceptibility data for 12 antimicrobial substances (benzylpenicillin, ampicillin/sulbactam, piperacillin/tazobactam, imipenem, meropenem, cefoxitin, metronidazole, moxifloxacin, clindamycin, doxycycline, tigecycline, eravacycline) were collected. Susceptibility testing showed low resistance to β-lactam/β-lactamase inhibitor combinations and no resistance to carbapenems and tigecycline. We observed moderate to high rates of resistance to moxifloxacin and clindamycin which differed depending on the methodology used. The essential and categorical agreement was over 90% for ampicillin/sulbactam, meropenem, moxifloxacin, and tigecycline. For metronidazole and clindamycin, the essential agreement was below 90% but the categorical agreement was near or above 90%. Penicillin presented with the lowest categorical agreement of 86.7% and a very high very major error rate of 13.3%. The resistance rates reported in this study are concerning and show the importance of routine susceptibility testing. Further investigations are necessary to determine the reason for high error rates and how to improve susceptibility testing of fastidious anaerobes.